UJI SPF (Sun Protaction Factor) KRIM EKSTRAK ETANOL DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) SECARA IN VITRO DAN IN VIVO PADA KULIT PUNGGUNG KELINCI - Sasangka, Nur Anggreini Dwi; Amin, Farizal Azizi; nopiyanti, vivin (Parapemikir : Jurnal Ilmiah Farmasi, 2024)
The harmful effects caused by solar UV radiation cause sunburn. Using sunscreen is one way to protect the skin from the harmful effects of UV rays. Binahong leaves (Anredera cordifolia (Ten.) Steenis) have alkaloids, flavonoids, tannins, saponins, steroids, and terpenoids which are helpful as sunscreens. This study aims to determine whether the extract and cream formula of binahong leaves has the potential as sunscreen in vitro and in vivo and the SPF, Tp(%), Te(%), and MED values. Binahong leaf extract was macerated with 96% ethanol. The SPF test uses a UV-VIS spectrophotometer with a 290-320 nm wavelength. Results were analyzed using ANOVA. They made sunscreen using various concentrations of binahong leaf ethanol extract 0.85, 0.95, and 1%. Sunscreen was tested in vitro and in vivo on rabbit test animals. The in vitro test results of the binahong leaf extract yield an SPF value of 45.7 ± 1.76 (ultra protection), Tp (%) of 10.39 ± 1.14 (fast tanning), and Te (%) of 15.49 ±1.74 (sunblock), in vivo, the extract has a MED value of 0 and FIII (1%) cream of binahong leaf extract is the best preparation because it has physical quality that meets the requirements, with an SPF value of 43.8 ± 1.88 (ultra protection), Te (%) was 18.96 ± 1.04, and Tp (%) was 28.00 ± 1.65, in vivo the extract had a MED value of 0.